Given
The function,
![y=-√(x-1)+5](https://img.qammunity.org/2023/formulas/mathematics/college/6kdh8t1g2cy1x7r30uocsqbb8of6e84l8y.png)
To find:
The end behaviour of the function.
Step-by-step explanation:
It is given that,
![y=-√(x-1)+5](https://img.qammunity.org/2023/formulas/mathematics/college/6kdh8t1g2cy1x7r30uocsqbb8of6e84l8y.png)
And, the graph of the above function is,
That implies,
From the graph,
As x tends to 1,
![\begin{gathered} y=-√(1-1)+5 \\ y=-√(0)+5 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m01df0m2i3tahw297j2wbawbyxf125zss3.png)
Also,
![\begin{gathered} y=-√(x-1)+5 \\ \Rightarrow y-5=-√(x-1) \\ \Rightarrow(y-5)^2=x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ifyzq1n2m2z1b1b78upjru0zi80rph85mw.png)
Then,
As x tends to infinity,
![\begin{gathered} (y-5)^2=\infty \\ y-5=\infty \\ y\rightarrow\infty \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7j7cjeqj20uan2qpkribqp9i57yluxoyj7.png)
Hence, the answer is option C),
![\begin{gathered} x\rightarrow\infty,\text{ }y\rightarrow\infty \\ x\rightarrow1,\text{ }y\rightarrow5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4bi7zj1ujx7ienox5zfrlg556o09cbk8tm.png)